Traditional Medicine Knowledge as Communal Intellectual Property in Aceh: How to Protect It and the Role of Women - Yulia Yulia; Jamaluddin Jamaluddin; Temitope O. Oloko; Aydan Mammadova (LAW REFORM, 2026)
Traditional medicinal knowledge is part of traditional knowledge and is also recognized as communal intellectual property, as stipulated in Article 18B paragraph (2) of the Indonesian Constitution concerning the traditional rights of communities, and Article 28I paragraph (3) of the Constitution regarding respect for cultural identity and the rights of traditional communities.This study aims to analyze the protection of traditional medicinal knowledge as communal intellectual property in Aceh and the role of women in managing traditional medicinal knowledge in Aceh. This research employs a qualitative method with an empirical legal approach, using both primary and secondary data. Primary data were collected through structured interviews with respondents and informants.The findings indicate that there is currently no protection for traditional medicinal knowledge as communal intellectual property (CIP) in Aceh, as it has not yet been documented or recorded. The Acehnese community preserves traditional medicinal knowledge orally, passing it down to the next generation within their families particularly among women who manage herbal recipes making this knowledge highly vulnerable to loss and difficult to protect from biopiracy. Women hold a strategic role as managers, inheritors, and innovators in the development of traditional medicinal knowledge, whether through family healing practices, customary rituals, or community-based treatments.